Design of human heartbeat monitoring system based on wireless sensor networks - Hidayaturrohman, Qisthi Alhazmi; Lukmana, M. Arifudin; Zaman, Akhmad Nidhomuz (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2023)
The IoT technology plays an important role in Industry 4.0 revolution. The IoT technology has potential to be implemented in the medical industry, especially for the development of telemedicine system. IoT able to send the medical sensor data wirelessly to the nearest medical facility like hospital. In this research, the author designed the heart beat monitoring system by using 802.11 communication protocol and simple web interface. The pulse sensor that used in this research was able to read the pulse rate of the human and convert it to BPM (beat per minute). It has 98.89% accuracy and 1.11% error compared to the smartwatch result. In the other hand, ESP-32 also implemented as the microcontroller as well as the sensor node of the system. It was able to send the data wirelessly from sensor node to the coordinator node. The coordinator node was also able to fetch the sensor data into the database using POST and GET method and then visualize the sensor data over web interface so the other users are able to see the visualization of the sensor data.